Kansas forestry - Reed, Elias W. (My University, 1892)
Introduction: Kansas is a part of what was once called the “Great American Desert” and portions of it are yet believed by many to be useless for anything but grazing. But let the person who has such an idea look at a map of Kansas, and he will be surprised to find that it is so well watered. He will wonder, perhaps, why there is no more timber; but if he thinks of the prairie fires which formerly swept over the hills and the countless herds of buffalos that trampled the streams, he can fully understand the cause of the almost treeless plains. The amount of timber in the state in 1873 was estimated at a little over two and one half million acres – less than five percent of the whole area. Compare this with twenty or fifty percent in some of the eastern states, and we can realize the barrenness of our state and the importance of forest culture. Important as it is to plant trees and preserve our nature forests, hundreds of acres of our best timber are being cut for posts and timber. Acres of young timber are being grabbed out so the land can be used for agricultural purposes. Near Oskaloosa the finest of young walnut trees are being cut and shipped to England.
Citation: Reed, Elias W. Kansas forestry. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Forestry; Conservation; Tree; Kansas; Green; Botany; Theses; Manuscripts (documents)